Sassy Mamas and Other Plays - Walker, Celeste Bedford (Book collections on Project MUSE., 2023)
Celeste Bedford Walker, one of the most accomplished contemporary playwrights in Texas, crafts dramas from history and everyday life that illuminate the African American experience in all its variety, tragedy, pathos, and hilarity. Collected here are five of her most acclaimed plays: Sassy Mamas, Greenwood: An American Dream Destroyed, Reunion in Bartersville, Distant Voices, and Camp Logan. The topics treated by Walker are timelier than ever. Sassy Mamas follows "three women of substance and of a certain age who flip the script on gender stereotypes and become involved with younger men." Greenwood: An American Dream Destroyed tells the powerful story of the horrific attack on the Greenwood District of Tulsa, Oklahoma, once known as the "Black Wall Street." In Reunion in Bartersville, described by Walker as "a comedy-mystery in two acts," the 50-year class reunion of Bartersville High School turns to hilarious suspense when an unexpected guest arrives. Recipient of a grant from the National Endowment for the Arts, Distant Voices "resurrects" persons buried in College Memorial Park, the second-oldest African American cemetery in Houston, to celebrate the wisdom of those gone before. Camp Logan is based on real-life events in Houston in 1917, when members of the highly decorated 24th Infantry Regiment were subjected to brutal Jim Crow treatment, resulting in a riot that left dozens dead and the execution of seventeen African American soldiers for mutiny. Readers and audiences should be prepared to laugh out loud, to be challenged, to be disturbed, and above all, to be enlightened by this poignant collection of plays.